PERANAN OLAH TUBUH TERHADAP TEKNIK TARI DALAM KARYA TARI AUTIS KARYA VIVI SUMANTI - Poppy Lisafri Yolanda; Indrayuda Indrayuda; Darmawati Darmawati (FBS Universitas Negeri Padang, 2012)
This article aims to describe the benefits of body movement toward a dance technique Autism arable Vivi Sumanti, a students of art department FBS UNP. This research is descriptive qualitative research method. Object of study is the work of dance Autism, data were collected through observation, library research and interviews. Data were analyzed through ethnographic analysis. The results were found, at the time of the initial drill choreographed to provide training if the body only of a general nature, such as strength, flexibility, endurance, and balance. However, the reality is if the body is generally not useful to the dance techniques desired by the choreographer. Because dance choreographer creates more movement traditional techniques that worked with modern dance, a blend of technique Jazz, Ballet, Headstand, and kayang. The body should be beneficial when the body work is done in accordance with the technique of dance choreographer wants. In the end, the body benefits obtained for Autism dancers just for strength and flexibility.